Studi Dasar Kesehatan Lingkungan di Kecamatan Hu’u, Sumbawa Barat, NTB, Indonesia: Bahasa Indonesia - Kharistanto, Robertus Tegar Kurnia; Aprilia, Hesti Dwi; Fahlevy, Karizma; Sembiring, Agustinus; Suroso, Adi (LRI Universitas Muhammadiyah Sorong, 2025)
Good environmental quality is essential to support the optimal life and development of communities. Hu’u District, Dompu Regency, possesses abundant natural resource potential; however, human activities, especially agriculture, can affect the local environmental conditions. This study aims to evaluate the environmental health status in Hu’u District, focusing on groundwater quality, soil, and air parameters based on the standards outlined in the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023. Sampling conducted during the wet season (February–March 2023) at nine groundwater locations, ten soil locations, and five air sampling sites around villages in Hu’u District. Physical, chemical, and microbiological analyses were performed to assess water and soil quality. The results showed that several groundwater parameters, such as color, turbidity, and total dissolved solids (TDS), exceeded the established thresholds, likely due to natural organic matter, mineral dissolution, and agricultural activities. Total coliform bacteria were detected at several points, indicating potential domestic waste contamination, although Escherichia coli was not found. Concentrations of heavy metals include Barium (Ba), Copper (Cu), and Zinc (Zn), in some soil locations exceeded quality standards, suspected to be associated with agricultural activities and active geological characteristics. Additionally, air quality for chemical parameters is classified as good, but CO concentrations need to be prioritized for monitoring as its potential to increase due to the burning of agricultural waste activities. These findings provide an important basis for developing adaptive environmental management policies in Hu’u to maintain ecosystem sustainability and community quality of life.